1996
DOI: 10.1038/bjc.1996.42
|View full text |Cite
|
Sign up to set email alerts
|

Application of the multidimensional fatigue inventory (MFI-20) in cancer patients receiving radiotherapy

Abstract: Summary In this paper the psychometric properties of the multidimensional fatigue inventory are established further in cancer patients. The MFI is a 20-item self-report instrument designed to measure fatigue. It covers the following dimensions: general fatigue, physical fatigue, reduced activity, reduced motivation and mental fatigue. The instrument was used in a Dutch and Scottish sample of cancer patients receiving radiotherapy. The dimensional structure was assessed using confirmatory factor analyses (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
202
1
19

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 382 publications
(231 citation statements)
references
References 12 publications
5
202
1
19
Order By: Relevance
“…Previous investigations have shown that women with breast cancer undergoing chemotherapy experience both disturbed sleep and increased fatigue [18,26,37,40,41,45]. The data from the current study showed that the women experienced both disturbed sleep and fatigue before they began chemotherapy.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Previous investigations have shown that women with breast cancer undergoing chemotherapy experience both disturbed sleep and increased fatigue [18,26,37,40,41,45]. The data from the current study showed that the women experienced both disturbed sleep and fatigue before they began chemotherapy.…”
Section: Discussionsupporting
confidence: 48%
“…One of the most frequent and disturbing complaints of patients with cancer is fatigue [37,40,41,45]. There is no universally accepted definition of fatigue, but what one descriptor often included is sleepiness during the day accompanied by poor sleep at night [23,45].…”
Section: Introductionmentioning
confidence: 99%
“…This test, which requires divided attention, sustained concentration and efficient information processing, has been shown to be sensitive to subtle neurocognitive deficits. In other patient samples PASAT scores have been found to mirror patients' self-reported difficulties (Johnson et al, 1994 (Fobair et al, 1986;Smets et al, 1996). Whether or not some common underlying physiological mechanism can be elucidated, this finding further underlines the importance of assessing patients who complain of cognitive dysfunction or fatigue for clinically significant and potentially remediable emotional disturbance.…”
Section: Discussionmentioning
confidence: 84%
“…Multi-Dimensional Fatigue Inventory (MFI) This 20-item Dutch instrument has been pretested in English in a mixed group of patients receiving radiotherapy in our department (Smets et al, 1995a(Smets et al, , 1996 (Bentall et al, 1993).…”
mentioning
confidence: 99%
“…It has been validated in both healthy and ill populations. The authors found the instrument to have good internal consistency, construct validity and convergent validity (37,49) in both Dutch and English. The MFI has been tested on radiotherapy patients, patients with chronic fatigue syndrome, psychology students, medical students, soldiers, and junior physicians (37).…”
Section: Multidimensional Fatigue Inventory (Mfi-20)mentioning
confidence: 99%